2001
DOI: 10.1038/sj.tpj.6500012
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate synthase gene polymorphism determines response and toxicity of 5-FU chemotherapy

Abstract: Thymidylate synthase (TS) catalyses the conversion of deoxy-uridylate to deoxy-thymidylate and is essential for DNA synthesis. The human TS gene promoter is polymorphic, having either double or triple tandem repeats of a 28-bp sequence. Here we determined the significance of this polymorphism in humans and its prediction for clinical outcome of patients with metastatic colorectal cancer treated with 5-fluorouracil. The TS mRNA level was analyzed using RT-PCR. Individuals homozygous for the triple repeat varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
324
7
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 530 publications
(355 citation statements)
references
References 18 publications
17
324
7
7
Order By: Relevance
“…DISCUSSION A number of retrospective studies have demonstrated that the TS expression is influenced by the VNTR located in the promoter of the TS gene. Pullarkat et al 26 found a 3.6-fold increase in TS mRNA levels in individuals homozygous for TS*3 compared to TS*2 homozygotes (p ϭ 0.004) and a 1.7-fold increase in patients homozygous for TS*3 with respect to patients heterozygous TS*2/ TS*3 (p ϭ 0.05). Their study also showed that, in 50 patients receiving 5-FU for metastatic colorectal cancer, there was a higher response rate in patients with low numbers of TS repeats (50% for *2/*2, 15% for *2/*3 and 9% for *3/*3).…”
Section: Correlation Between Ts Genotype and Outcome Of Chemotherapymentioning
confidence: 97%
See 1 more Smart Citation
“…DISCUSSION A number of retrospective studies have demonstrated that the TS expression is influenced by the VNTR located in the promoter of the TS gene. Pullarkat et al 26 found a 3.6-fold increase in TS mRNA levels in individuals homozygous for TS*3 compared to TS*2 homozygotes (p ϭ 0.004) and a 1.7-fold increase in patients homozygous for TS*3 with respect to patients heterozygous TS*2/ TS*3 (p ϭ 0.05). Their study also showed that, in 50 patients receiving 5-FU for metastatic colorectal cancer, there was a higher response rate in patients with low numbers of TS repeats (50% for *2/*2, 15% for *2/*3 and 9% for *3/*3).…”
Section: Correlation Between Ts Genotype and Outcome Of Chemotherapymentioning
confidence: 97%
“…Patients with *2/*2 genotype have a good prognosis, but patients with *3/*2 genotype are sometimes included in the good prognosis group 27 and other times in the intermediate or bad prognosis group. 12,26 In a recent work, Uchida et al 29 reported that the loss of heterozygosity at the TS locus in tumor samples of colorectal cancer patients treated with fluoropyrimidine therapy affects tumor response and survival in those patients with a heterozygous TS*2/*3 genotype. In 17 of 22 of these heterozygous cases, a LOH was demonstrated in tumor tissues The authors reported that the response rate of the TS*2/loss tumor genotype patients was 80% and that only 1 of 7 tumors with a genotype of *3/loss showed a response.…”
Section: Correlation Between Ts Genotype and Survivalmentioning
confidence: 99%
“…43 In general, most published data support that patients with metastatic disease and low TS expression showed a trend toward better response to chemotherapy and longer survival, but possibly more severe toxicities, than did the high TS expression counterpart genotypes (for example, 3R/ 3R, þ 6 bp/ þ 6 bp), both in the adjuvant and advanced settings. 34,44,45 This trend was confirmed in a meta-analysis reviewing the association of TS expression and prognosis in advanced and localized CRC, but there was evidence of heterogeneity and possible publication bias. 46 Therefore, TS was not recommended as a prognostic or predictive tumor marker by the American Society of Clinical Oncology in the 2006 Update of Recommendations for the Use of Tumor Markers in Gastrointestinal Cancer.…”
Section: Cytotoxics: Pharmacogenetics and Molecular Markersmentioning
confidence: 86%
“…34,35 In contrast, 2R/ 2R genotype has been associated with low levels of TS expression and better clinical outcome to therapy. 35,36 In addition to the above genotypic groups, a single-nucleotide polymorphism (SNP; G-C), observed at the 12th position of the second repeat of the 3R allele, at its upstream stimulatory factor family E-box elements, reduces its translational activity and causes low TS expression and therefore an altered outcome similar to 2R.…”
Section: Cytotoxics: Pharmacogenetics and Molecular Markersmentioning
confidence: 99%
“…An association between the genotype of the TS enhancer region and response and toxicity with 5-FU-based therapy in patients with colorectal cancer has been reported previously. [29][30][31][32][33][34][35][36][37][38][39] : patients who are homozygous for the double-tandem repeat have a lower TS protein content and a higher likelihood of response, but a greater risk of toxicity. MTHFR is involved in the regeneration of 5 methyltetrahydrofolate from 5,10 methylenetetrahydrofolate.…”
Section: Discussionmentioning
confidence: 99%